Comparative Efficacy of preservative vs. isotonic fluids in liver transplantation: A scoping review - Muhammad Salman; Saira Imtiaz; Talha Bukhari; Irfan Ahmed (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the comparative efficacy of preservative solutions versus isotonic fluids in living donor liver transplantation. Method: The scoping review was conducted from June 1, 2024, to January 1, 2025, and comprised comprehensive literature search across PubMed, Scopus, Cochrane Library and Cumulative Index to Nursing and Allied Health Literature databases for randomised/non-randomised trials, observational studies and case series comparing preservative solutions and isotonic fluids in living donor liver transplantation cases involving adults that were published in the English language up to October 2023.. After data extraction, the volume and type of evidence was noted, consistent themes were identified, and critical gaps were highlighted. Results: Of the 2,131 studies screened, 51(2.4%) were assessed for eligibility, and, of them, 1(1.9%) was reviewed in detail, involving 80 adult living donor liver transplantation recipients, divided equally into histidine-tryptophanketoglutarate and non-histidine-tryptophan-ketoglutarate groups. Outcomes, including early allograft dysfunction, postoperative complications, hospital stay, and 1-year survival rates, were comparable between the two groups. The non-histidine-tryptophan-ketoglutarate approach significantly reduced direct costs by 2,000 per graft. Conclusion: Cold normal saline appeared safe and cost-effective for select living donor liver transplantation cases with short ischaemia time and minimal back-table work, potentially reducing costs compared to histidinetryptophan- ketoglutarate. Key Words: Liver transplantation, Saline solution, Cost-effectiveness, Preservative solutions, Isotonic fluids, Graft survival, Scoping review.